Konsep Sila dan Akhlak: Satu Analisis Awal - Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
The word sila in Buddhism and akhlaq in Islam are theological term. Normally, the words referred as an ethic and attitude. Besides, many of the Western Scholars put them synonym. Thus, the concept and why are they synonym are not known. Therefore, this article attempts to elaborate the two words in various taakulan based on theories which already exist.